O ensino de língua portuguesa: um olhar sobre a leitura - Izidoro, Solange (2010)
Given the state of reading in Brazil, that is more related to the failure to success, this work has the objective to analyze, from the stand point of the of the conception of reading socialinternationalcognitive, the Teacher´s Notebooks of SEE SP for the final grades of Elementary School (ES) 8TH grade and for the final grades of High School (HS) - 3RD grade and check in all the contents and activities proposed in the Notebooks, the place occupied by the reading in them. The analyzes based on the hypothesis that in most of the materials, more precisely the books, used in classrooms by teachers and students, the reading seems to be a practical focus only on the decoding, reproduction of an already-said, also be used for setting the grammatical rules. From studies about reading, addressing the notion of the concept of reading, the historical evolution of the same and some conceptions of reading. Then, we reflect about the proposal for reading practice guided by the National Curriculum Standards (NCS) of the Elementary School (ES) and the High School (HS) and, finally, we analyze the place of reading in the Teacher's Notebook cited above. This research is concerned with shedding light on a reflection about the reading, with the intention of rethinking their teaching and practice